Synthesis, Characterization and Antibacterial Activity of Some Lanthanide(III) Chloride Complexes of 2-(N-indole-2-one)amino-3-carboxyethyl-4,5,6,7- tetrahydrobenzo[b]thiophene - THANKAMONY, M.; MOHANAN, K. (Asian Journal of Chemistry, 2010)
Complexes of La(III) ,Ce(III), Pr(III) ,Nd(III ),Sm(III), Eu(III), Gd(III), Dy(III), Yb(III) and Lu(III) with 2-(Nindole-2-one)amino-3-carboxyethyl-4,5,6,7-tetrahydrobenzo[b]thiophene (ISAT) formed by the condensation of isatin and 2-amino-3-carboxyethyl-4,5,6,7-tetrahydrobenzo[b]thiophene, were synthesized and characterized on the basis of elemental analysis, molar conductance measurements, magnetic susceptibility data, UV-vis, IR and NMR spectral studies. The spectral data reveal that the ligand acted as neutral tridentate coordinating to the metal ion through the azomethine nitrogen, ester carbonyl and carbonyl oxygen of the isatin moiety. A coordination number of six has been proposed for the complexes. The lanthanum(III) complex was subjected to X-ray diffraction studies. The ligand and the complexes were screened for their antibacterial activity and it has been observed that the complexes are more potent bactericides than the ligand.